A distributed adaptive local searching algorithm for wireless sensor network localization. (October 2016) - Hernández, Oscar Osvaldo Saldaña; Cota-Ruiz, Juan; Gonzalez-Landaeta, Rafael; Sifuentes, Ernesto
The location of sensors represents a relevant attribute in wireless sensor networks. In this article, we propose a distributed range-based localization algorithm for wireless sensor network. The algorithm is mainly based on an adaptively local circular searching area where each unknown sensor must find inside a position that minimizes the error distance with neighboring sensors using a local function. The new position of a sensor is broadcast to neighboring sensors allowing collaboratively to other sensors re-estimate their new positions. The iterative process is repeated until a stopping criterion is reached. The performance of the proposed algorithm is evaluated and compared with other state-of-the-art algorithms, and results indicate that the approach overcomes the other methods in both accuracy and time of convergence.